Implementasi Teknologi Digital pada Pengelolaan UMKM Cahaya Kemilau (Pengrajin Tenun Songket Melayu Riau) - Purwati, Astri Ayu; Hamzah, Muhammad Luthfi; Irman, Mimelientesa; Rahman, Sarli (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Cahaya Kemilau is one of the UMKM craftsmen of Riau Malay songket weaving in Pekanbaru. Some of the partner problems in this activity consist of: 1) production equipment that is still inadequate to increase production output, 2) traditional recording system that allows human error and is difficult to control, 3) traditional marketing system so that it has not touched potential customers from out of town to abroad. Some of the solutions offered to partners to solve existing problems include: 1) Adding weaving equipment 2) Designing an Android-based sales system 9) Making digital marketing (websites, social media and e-commerce of light sheen). Through this activity, several problems that became a priority for Cahaya Kemilau in producing Riau Malay songket weaving and also expanding its market distribution have been resolved with the presence of weaving equipment assistance that has been provided to seek to increase weaving production. For digital-based sales, currently Tenun Cahaya Kemilau is able to do marketing throughout the archipelago and even from outside Indonesia through online sales of websites, shopee and Instagram. Management management has become even better with the existence of an Android-based sales system. Traditional financial records, which were originally very vulnerable to missing records and human errors, are now easier to manage and monitor properly by the management.